The Hyposodic Diet Reduces Urinary Supersaturation Index of Calcium-Oxalate Salts in Calcium-Oxalate Stone Formers with Metabolic Syndrome. Issue 1 (January 2017) - De Pascale, Francesca; Di Cola, Michele Schiano; Muscariello, Riccardo; De Filippo, Gianpaolo; Strazzullo, Pasquale; Rendina, Domenico
Background: Nutritional factors play a key role in the pathogenesis of both metabolic syndrome (MS) and calcium-oxalate (CaOx) nephrolithiasis (NL), two clinical entities strictly related. A reduction in dietary salt intake was universally recommended for treatment and prevention of MS and CaOx-NL. The aim of this study was to assess the efficacy of an hyposodic and normocalcic 7-days diet on the urinary supersaturation index of CaOx salts (APCaOx ), which is the driving force for CaOx crystallization and aggregation. Patients and Methods: 18 patients with CaOx-NL and MS were evaluated on free diet and after 7 days of hyposodic and normocalcic metabolic diet. The adherence to prescribed metabolic diet was evaluated measuring the 24 h urinary sodium excretion before and after the diet: all enrolled patients showed an urinary sodium excretion <100 mmol/24 h after the diet. Results: In addition to the decrease in urinary sodium excretion (185.2 ± 9.9 vs 89.2 ± 9.6 mmol/24 h; p<0.01), we observed also a reduction in the 24 h urinary calcium (6.49 ± 0.09 vs 5.31 ± 0.25 mmol/24 h; p<0.01) and oxalate excretions (0.44 ± 0.06 vs 0.30 ± 0.04 mmol/24 h; p<0.01) and in the 24 h urinary volume (1.85 ± 0.09 vs 1.61 ± 0.09 mmol/24 h; p<0.01). APCaOx declined significantly after the diet (1.48 ± 0.09 vs 1.12 ± 0.05; p<0.01). Discussion: The reduction in dietary salt intake significantly reduces the APCaOx index and could play an important role in the prevention of CaOx-NL associated to MS.